Experimental and theoretical approaches on mechanical evaluation of Y123 system by Lu addition - Turkoz, M. B.; Nezir, S.; Ozturk, O.; Asikuzun, E.; Yildirim, G.; Terzioglu, C.; Varilci, A. (Springer Science and Business Media LLC, 2013)
This work is the continuation of a systematic study on the characterization of the Lu-added Y123 bulk superconducting materials prepared by the nitrate compounds and derivatives at 970 °C for 20 h. In this part, the effect of Lu inclusions on the physical and mechanical properties of the Y123 superconductors is examined with the aid of microhardness measurements performed at various applied loads in the range of 0.245–2.940 N. The microhardness measurement results allow us to determine the important mechanical characteristics such as Vickers microhardness, elastic (Young’s) modulus, yield strength and fracture toughness values being responsible for the potential industrial applications. It is found that all the properties given above are strongly dependent upon the Lu concentration in the Y123 matrix. Especially, Vickers microhardness (H v ) values of the samples studied in this work are found to suppressed considerably with the enhancement of the Lu addition in the system due to the degradation in the connectivity between superconducting grains. Moreover, the H v values of the pure Y123 sample are observed to increase with increasing the applied load whereas those of the Lu-doped superconducting materials are obtained to decrease with the load. In other words, the pure sample exhibits the reverse indentation size effect (RISE) behavior while the others obey the indentation size effect (ISE) feature, confirming the degradation in the mechanical properties with the Lu inclusions in the Y123 matrix. In addition, the microhardness measurement results are estimated using the 5 different models such as Meyer’s law, proportional sample resistance model, elastic/plastic deformation model, Hays–Kendall (HK) approach and indentation-induced cracking (IIC) model. According to the results obtained from the simulations, of the mechanical analysis models, the Hays–Kendall (HK) approach is determined as the most successful model for the description of the mechanical properties of the Lu-doped superconducting materials (exhibiting the ISE behavior) where both the both the reversible (elastic) and irreversible (plastic) deformations are produced. On the other hand, the IIC model is found to be superior to other approaches for the pure sample (presenting the RISE feature) where the irreversible deformation becomes more and more dominant compared to the reversible deformation.
Keywords: Electrical and Electronic Engineering; Condensed Matter Physics; Atomic and Molecular Physics, and Optics; Electronic, Optical and Magnetic Materials